Tantangan dan Peluang Pelibatan Orang Tua Dalam Manajemen Pendidikan di TK IT Tamrinul Aulad Manyargading Kalinyamatan Jepara - Andriyani, Ema; Ruviyana Naviya Safitri; Fu’ad Arif Noor (EDUCATE : Journal of Education and Culture, 2025)
This study aims to identify the challenges and opportunities for parental involvement in educational management at TK IT Tamrinul Aulad. Parental involvement is an important factor in supporting the quality of early childhood education, but often faces obstacles such as time constraints, ineffective communication, and different understandings between schools and parents. The research method used is qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that parental involvement makes a positive contribution to educational management, especially in terms of communication, support for home learning, and participation in decision making. However, the main challenges faced are the busyness of parents and the lack of structured programs to accommodate their involvement. Opportunities include the development of more effective communication media and the implementation of joint activities that can increase synergy between schools and parents. This study recommends increasing collaboration and innovation efforts in educational management to optimize the role of parents in supporting the success of education at TK IT Tamrinul Aulad.